Reimagining Singapore Self and Society in Contemporary Art - Lum, Chee-Hoo.; Lizeray, Juliette Yu-Ming.; Twardzik Ching, Chor Leng. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book approaches the subject of contemporary art by exploring the social embeddedness and identities of Singaporean artists. Linking artistic processes and production to both personal worlds and wider issues, the book examines how artists negotiate their relationships between self and society and between artistic freedom and social responsibility. It is based on original research into the discourses and artistic practices of local artists, with a special focus on emerging artists and artists whose work and perspectives engage with questions of identity. Reimagining contemporary Singapore and their place within it, artists are asserting their multiple and heterogeneous self-identities and contesting hegemonic norms and notions, as they negotiate and adapt to the world around them. Relevant to art and cultural scholars interested in the relationships between self and society, between artistic freedom and social responsibility, this book also presents a new means of understanding contemporary Singapore and Singaporean identity through the lens of its artists. This book is relevant to students and researchers in the fields of cultural studies, media studies, art, sociology of art, arts education, and race and ethnicity studies.
1. Identity Negotiation in Context: Three Artists and Their Works -- 2. Voicing the Nation through Visual Arts Education: Pedagogical Cues from Singapore Contemporary Artists -- 3. Ritual Forage: Finding the Self in Mystical Realms -- 4. Soundscapes of Our Lives: Lessons from Singapore Contemporary Artists -- 5. Social Practice Art in Singapore: Creative Approaches Towards Participation and Social Amelioration.
Keywords: Identity politics; Ethnology -- Asia; Culture; Arts; Music; Social sciences; Race; Identity Politics; Asian Culture; Arts; Music; Society; Race and Ethnicity Studies